Exploring the Role of Social Imagination in Shaping Pedagogical Practices and Critical Thinking in Indonesia - Sapia, Tasya; Luhukay, Calvin; Ngarbingan, Novena Kristi (Eastasouth Institute, 2025)
This qualitative study explores the role of social imagination in shaping pedagogical practices and enhancing critical thinking in the Indonesian educational context. Drawing on in-depth interviews with five key informants—including teachers, a curriculum expert, and education practitioners—the research investigates how educators conceptualize social imagination and incorporate it into their teaching strategies. The findings reveal that social imagination fosters student engagement, empathy, and the capacity to question societal norms, all of which are foundational to critical thinking. Educators employ various imaginative approaches, such as storytelling, role-play, and community-based projects, to connect learning with real-world issues. However, the implementation of such approaches is often constrained by rigid curricula, cultural hierarchies, standardized assessments, and limited institutional support. Despite these challenges, the study concludes that social imagination remains a vital pedagogical tool for transformative education in Indonesia, offering pathways to more reflective, inclusive, and critical forms of learning.